Determinación de la dieta del mapache (Procyon lotor hernandezii Wagler, 1831) en la Costa Sur de Jalisco, México - Guerrero, Sergio; Sandoval, Ma. Rosario (Instituto de Ecología, A.C., 2000)
In this work, we documented the food habits of the Raccoon (Procyon lotor hernandezii) in the zone of Tenacatita, in the State of Jalisco. We collected scats each month, from March 1994 to December 1995. We determined that plant material was first in importance at 41.0%, the next was insects with 18.4%, and crustaceans with 17.8% of relative frequency of occurrence (RFO). The plants with higher frequencies were guazima (Guazuma ulmifolia), guamuchil (Pithecellobium dulce), grasses (Gramineae), papaya (Carica papaya) and coconut (Cocus nucifera). Four cultivated plants were found in the scats: papaya (3.93%), coconut (1.54%), corn (1.03%) and mango (0.68%), but their RFO was not high. Of the insects consumed, grasshoppers (Acrididae), beetles (Scarabaeidae), crickets (Grillidae), and ants (Formicidae) predominated. Seasonal variations in the RFO of plant material and insects were observed. The diversity of food items overall was H’= 1.36.